ANALISIS JALUR KRITIS UNTUK MENGATASI KETERLAMBATAN PROSES PEMASANGAN PRODUK INTERIOR FURNITURE DENGAN METODE PERT PADA SALAH SATU PROYEK PT PAP CABANG BANDUNG - Nurendi Ibnu Hindar (Operations Excellence: Journal of Applied Industrial Engineering, 2014)
Abstract. This thesis aims to analyze the critical path in the process of installationof one project PT PAP branch Bandung. This study uses a network diagram(PERT) to identify the critical path on each element of the work. The number ofproducts in the studied projects totaling 13 units of product. The initial step in thisresearch by calculating the standard time of the measurement of working timeevery element of the process to 13 the number of products in the studied projects.Critical path analysis using QM program for Windows. Analysis of the criticalpath in the PERT method provides the possibility of project completion fastercompared to before analysis. Identify the cause of the problem of delays in thecompletion of the entire project using the RCA (Root Cause Analysis). There aretwo main problems based on the Pareto diagram are the problems andshortcomings rework delivery. The main factor of rework problem is theweakness of the monitoring system and communication supervisor and the limitednumber of senior artisan. Improvement efforts undertaken in this research is toincrease communication and monitoring system with regular reports and conductskills training for junior builders.Keywords: Project Management, Measurement of working time, PERT method,RCA